Physiotherapy in the context of palliative care in oncology: a pooled analysis - Canto, Claudia Melo; Prestes, Yandra Alves; Lucena, Maria Gabriela de Andrade; Campos, Hércules Lázaro Morais (Brazilian Journal of Oncology, 2021)
Objective: To document the role of physiotherapy in the context of palliative care in cancer through an integrative literature review, as the prevalence and survival of cancer are increasing and physiotherapy can significantly contribute to the treatment of these patients. Methods: A search was made in the literature for scientific articles that substantiated the physiotherapist's role in palliative care in oncology, and an assessment of the methodological quality of the selected clinical trials. Results: Studies demonstrate positive results, as they propose effective protocols that mostly include exercises in different modalities associated or not with other resources such as PNF, TENS, manual therapy, ultrasound, thermotherapy, acupuncture, and oxygen therapy, which help in reducing symptoms such as cancer fatigue, pain, and dyspnea, improving the patient's quality of life. The average score for clinical trials was reasonably low. Conclusion: The results reaffirm the importance of physiotherapeutic interventions in cancer patients receiving palliative care.
Keywords: Cancer; Physiotherapy; Palliative care; Physiotherapy modalities.